Pharmacy Philosophy in the Law of Power: The Morality of Pharmaceutical Ethics towards Rhetoric of Logic - Hakim, Adiyansyah Lukman; Prasetyawan, Fendy; Saristiana, Yuneka; Muslikh, Faisal Akhmal; Dhafin, Anis Akhwan; Mildawati, Ratna; Arifin, Candra; Rofiq, Abd (PT FORMOSA CENDEKIA GLOBAL, 2023)
Pharmacy's evolution relies on technical and philosophical aspects. Research delves into the intricate link between pharmaceutical philosophy and legal power, emphasizing moral values in daily practice. The study aims to enhance policies, regulatory frameworks, and awareness, optimizing pharmacy's pivotal role in healthcare services. The results of this study depict an investigation and comprehension of the close interconnection between the philosophy of pharmacy, the law of power, the morality of pharmaceutical ethics, and rhetorical logic. A profound integration of these four aspects can provide a solid foundation for the development of ethical policies, maintaining the integrity of the pharmacy profession, and maximizing benefits for society. A deeper understanding of the complexity of these relationships can help shape a more sustainable and ethical future in the field of pharmacy. The findings of this research depict the complexity of these relationships, highlighting that deep integration can provide a solid foundation for ethical policies and the sustainable future of pharmacy